Pragmatic Dimensions in Selected Models of Sufi Poetry - Saleem, Anmar Dawood (Journal of Tikrit University for Humanities, 2025)
Saussure's distinction between the potential existence of language and its actual manifestation, or more conceptually, between langue and parole, sparked an intellectual revolution in linguistic research. However, linguistic studies long remained confined to the sentence level, examining language in and for itself, with rare exceptions, largely avoiding the complexities of understanding language within its context and the profound influence this context exerts on a more precise comprehension of meaning. Subsequently, scholars began to study language beyond its formal boundaries, observing its interaction with surrounding contexts, whether linguistic or extra-linguistic. Studying language within its social context reveals new dimensions and more objective concepts. A significant outcome of studying language in context was the emergence of a linguistic theory known as Pragmatics. One of its foundational pillars is the Speech Act Theory, developed by the linguists John Austin and John Searle. The core of this theory shifts focus from what is said to what is accomplished. A speech act typically progresses through three phases: the locutionary act (the act of saying), the illocutionary act (the intended force), and the perlocutionary act (the effect achieved). Undoubtedly, we often find ourselves unable to express our intentions directly for various reasons. This is a phenomenon we will observe and uncover in Sufi poetry, where poets frequently employ indirect speech acts to influence their audience without explicitly disclosing their intentions.